Mucormycosis: New Developments into a Persistently Devastating Infection - Danion, François; Aguilar, Claire; Catherinot, Emilie; Alanio, Alexandre; DeWolf, Susan; Lortholary, Olivier; Lanternier, Fanny (Seminars in Respiratory and Critical Care Medicine, 2015)
Mucormycosis is a rare, though increasingly prevalent, life-threatening fungal disease caused by Mucorales. The incidence has increased over the last decade and its mortality remains high at around 50%. Mucormycosis occurs mostly in patients with diabetes mellitus and/or in the context of immunosuppression resulting from chemotherapy for hematological malignancy, hematopoietic stem cell transplantation, or solid-organ transplantation. In this situation, lung and rhino-orbito-cerebral infections are the most frequent localizations of the disease. Prompt initiation of an effective treatment is essential to decrease mortality. However, mucormycosis and aspergillosis share close clinical and radiological features. Invasive procedures such as bronchial endoscopy and/or lung biopsy are necessary to confirm diagnosis, as no indirect tests are yet validated. Therefore, the challenge is to minimize the delay in diagnosis. When present, the reversed halo sign on CT scan is suggestive of mucormycosis. Quantitative polymerase chain reaction is a new promising approach to detect Mucorales DNA in serum and new molecular tools are available to detect Mucorales in tissues as well as to specify species. Recommendations from ECIL and ECMM/ESCMID have recently been published on management of mucormycosis. The recommended treatment is an amphotericin B lipid formulation in combination with surgery and modification of risk factors. High-dose (10 mg/kg) of liposomal amphotericin B is recommended in case of neurological involvement and posaconazole for maintenance therapy. Place of isavuconazole as well as posaconazole new formulations (tablets and intravenous) in first line treatment have to be defined. Improved radiologic descriptions of mucormycosis and new molecular tools may be key elements to help with rapid diagnosis in the future. Clinical trials are warranted to improve therapeutic success and hopefully survival.
Keywords: mucormycosis; pulmonary mucormycosis; Mucorales; mycosis; review; treatment